Synthesis and gas permeation properties of thermally rearranged poly(ether-benzoxazole)s with low rearrangement temperatures. Issue 30 (5th May 2020) - Lu, Yunhua; Zhang, Jianhua; Xiao, Guoyong; Li, Lin; Hou, Mengjie; Hu, Junyi; Wang, Tonghua
Abstract : A series of poly(ether-benzoxazole)(PEBO) for gas separation were prepared from 9, 9-bis[4-(4-amino-3-hydroxylphenoxy)phenyl]fluorene based hydroxyl-containing poly(ether-imide)s (HPEIs) with low rearrangement temperatures. Abstract : The diamine monomer, 9, 9-bis[4-(4-amino-3-hydroxylphenoxy)phenyl] fluorene (bis-AHPPF) was successfully synthesized according to our modified method. A series of hydroxyl-containing poly(ether-imide)s (HPEIs) were prepared by polycondensation of the bis-AHPPF diamine with six kinds of dianhydrides, including 1, 2, 3, 4-cyclobutanetetracarboxylic dianhydride (CBDA), pyromellitic dianhydride (PMDA), 3, 3′, 4, 4′-biphenyl tetracarboxylic diandhydride (BPDA), 3, 3′, 4, 4′-oxydiphthalic anhydride (ODPA), 3, 3′, 4, 4′-benzophenonetetracarboxylic dianhydride (BTDA) and 4, 4′-(hexafluoroisopropylidine)diphtalic anhydride (6FDA) followed by thermal imidization. The corresponding thermally rearranged (TR) membranes were obtained by solid state thermal treatment at high temperature under a nitrogen atmosphere. The chemical structure, and physical, thermal and mechanical properties of the HPEI precursors were characterized. The effects of heat treatment temperature and dianhydrides on the gas transport properties of the poly(ether-benzoxazole) (PEBO) membranes were also investigated. It was found that these HPEIs showed excellent thermal and mechanical properties. All the HPEI precursors underwent thermal conversion in a N2 atmosphere with low rearrangement temperatures. The gas permeabilities of the PEBO membranes increased with the increase of thermal treatment temperature. When HPEI–6FDA was treated at 450 °C for 1 h, the H2, CO2, O2 and N2 permeabilities of the membrane reached 239.6, 196.04, 46.41 and 9.25 Barrers coupled with a O2 /N2 selectivity of 5.02 and a CO2 /N2 selectivity of 21.19. In six TR-PEBOs, PEBO–6FDA exhibited the lowest rearrangement temperature and largest gas permeabilities. Therefore, thermally rearranged membranes from bis-AHPPF-based HPEIs are expected to be promising materials for gas separation.